An Approach to Tentative Reference Levels Setting for Nanoparticles in the Workroom Air Based on Comparing Their Toxicity with That of Their Micrometric Counterparts: A Case Study of Iron Oxide Fe3O4. (7th August 2012) - Katsnelson, Boris A.; Privalova, Larisa I.; Kuzmin, Sergey V.; Gurvich, Vladimir B.; Sutunkova, Marina P.; Kireyeva, Ekaterina P.; Minigalieva, Ilzira A.
Abstract : We overview the state of the art in the field of safe exposure levels setting for nanomaterials together with the previously published results of our experimental investigations characterizing comparative toxicity of the iron oxide Fe 3 O 4 (magnetite) in the form of microparticles and nanoparticles of different size and comparative activity of the defensive alveolar phagocytosis response to their pulmonary deposition. An approach to the substantiation of acceptable workplace exposure limits of metallic nanoparticles is discussed and, specifically, the tentative reference level for magnetite nanoparticles is recommended.